Stenosis simulation of femoral arteries using an adaptive 3D-printed actuator (Transactions on Additive Manufacturing Meets Medicine, 2021)
Motivated by the need for a simulator for varying degrees of vascular stenosis and different stenosis geometries, a pneumatic actuator was conceived and developed using additive manufacturing.  This actuator includes flexible and rigid parts.  The flexible components yield to incoming air pressure, so varying degrees of stenosis can be simulated based on the air pressure used.   The primary benefits of such an actuator are the lack of artifact-causing metal parts and the design flexibility additive manufacturing allows. Thus, such an actuator is useful in cardiovascular studies using MRI, CT, or MPI, as various stenosis geometries and degrees of vascular stenosis can be simulated.
Keywords: vascular model; vascular stenosis; adaptive simulator; stenosis simulation; peripheral arterial disease